Optimalisasi Produksi Susu Kerbau Dalam Meningkatkan Gizi Masyarakat Di Desa Sangiang Kecamatan Wera - Wandira, Ica Ayu; Dohi, Muhammad; Haryanto, Haryanto; Sadia, I Nyoman (Universitas Mataram, 2025)
This community service activity aims to inform the community about the importance of milk as a source of family nutrition, encourage the use of local livestock milk for this purpose, demonstrate the process of transforming buffalo milk into palopo, and highlight the economic benefits of livestock milk for improving farmers' incomes. This initiative addresses several issues: low public awareness of milk's health benefits and nutritional value, farmers' reluctance to milk lactating buffaloes due to concerns that this will deprive calves of their mother's milk, and the fact that milk is often wasted or not processed into other products. Additionally, there is a lack of familiarity with simple milk-processing technologies. To address these problems, the community service team from the Dairy Animal Science Department at the Faculty of Animal Husbandry, Mataram University, will conduct outreach and training activities focused on using local buffalo milk to increase family income and nutrition. The service activity, held on June 1, 2024, involved 25 participants, including housewives, buffalo breeders, and members of the general public. The activities included lectures, discussions, and hands-on training in making palopo. As a result of this initiative, the community gained a better understanding of milk's role in family nutrition, adopted the use of local livestock milk, and learned how to process buffalo milk into palopo.